English for Gamers: Level Up Your Language Skills and Connect Globally - Bayu Grendo Sigarete; Fini Widya Fransiska (Jurnal Pengabdian Masyarakat, 2024)
The integration of gaming into English language learning is gaining increasing attention as an innovative method for improving language skills. This research explores how the use of games, especially MMORPGs (Massively Multiplayer Online Role-Playing Games), can facilitate English language acquisition through the interactions required in game contexts. The game allows players to communicate in English in real-time, improving their language skills through practical application in high-pressure situations. Studies show that gamers often have better language skills compared to non-gamers, especially in vocabulary and writing skills. Additionally, the motivation triggered by the fun and interactive aspects of games can reduce affective barriers, such as anxiety, that are often encountered in traditional language learning. Through analyzing language features in gaming communities, learning materials can be designed to suit students' experiences and interests, making them more relevant and engaging. This research highlights the potential of games as an effective language learning tool, offering a new context for language acquisition that may not be achieved with conventional methods.